Structure and dynamics of poly(9,9-dioctylfluoren-2,7-co-benzothiadiazole) (F8BT) and correlations with its electrical properties - Faria, Gregório Couto (2011)
The PHD project has two main goals. The first one is specifically related to investigations on molecular dynamics, structural conformations and packing of polyfluorene-based polymers. For this purpose, Wide Angle X-Ray Diffraction (WAXD), Solid-State Nuclear Magnetic Resonance (NMR) and Dynamical-Mechanical Thermal Analysis (DMTA) are being used as the main techniques. The second goal is to correlate molecular phenomena, as characterized in the first part, with opto-electronic properties of polyfluorene when used as active layer in an electronic device, such as a Polymer Light-Emitting Diode (PLED). In the second part, fabrication of devices and their electrical characterization as a function of temperature are the main objectives. Impedance Spectroscopy, Current-Voltage characterization of the devices and Time-Of-Flight (TOF) techniques are among the main techniques to be used in the second part of the project. Therefore, the project combines fundamental studies on molecular dynamics with technological performance of organic electronic.